Changes in molecular species of triacylglycerols during frying - Gary Dobson; william w. Christie; M. C. Dobarganes (Grasas y Aceites)
The loss of specific molecular species of triacylglycerols from sunflower, high-oleate sunflower and palm oils has been investigated in commercial frying operations and simulated frying experiments. The non-oxidized triacylglycerols were isolated and molecular species separated by silver ion highperformance liquid chromatography. Linoleate-containing species were lost more rapidly than those containing oleate, as expected. However, all species were liable to oxidation and those containing oleate were lost more rapidly than might have been anticipated. It is suggested that oxidation of linoleate is the probable initiation step, but then the reaction can be propagated readily to all unsaturated species.